The Influence of Cattle Breeder Caracteristics on Their Involvement in the Farmer Group in the Rural Area - A. Asnawi; . Hastang (Jurnal Ilmu dan Teknologi Peternakan, 2015)
The aim of this research was to study the influence of cattle breeder caracteristics which consisted of age, education, and breeding experience on their involvement in the farmer group in the rural area. This research was conducted in Bone Regency, South Sulawesi. Population in this research was all of beef cattle breeders in that regency whether they already involved in the group or not. The total number of the sample was 88 farmers. The experiment used descriptive statistics to analyze characteristics of the breeders and multiple regression analysis to examine the influence of breeders’ caractersitics on their involvement in the farmer group. The results of this study indicated that age and education influenced their involvement on farming group in the rural area and positively correlated, while experience in breeding did not have a significant effect (P>0.05). This implies that the older the breeder and the higher education they have, the higher their awareness to be involved in the farmer group.